APPLICATION OF SIX SIGMA METHOD EVALUATING THE QUALITY OF PERIPHERAL BLOOD CELL TESTING AT PHUONG CHAU INTERNATIONAL HOSPITAL - Thành Trí, Võ; Thụy An, Bùi; Trung Tín, Lê; Phước Lợi, Lê; Thị Bảo Hà, Nguyễn (Tạp chí Sức khỏe và Lão hóa, 2025)
The Six Sigma approach enables laboratories to objectively evaluate analytical performance, refine IQC protocols, and establish suitable IQC frequencies. This study aimed to evaluate the quality and optimize the IQC procedure for selected hematology tests on the Advia 2120i automated hematology analyzer. A cross-sectional descriptive study was conducted using internal quality control and external quality assessment data from April 2024 to December 2024 at Phuong Chau International Hospital. The results showed that WBC and PLT achieved sigma values >4 at all three IQC levels. HGB had sigma values ranging from 3 to <6, while RBC had sigma values between 2 and <4 across all three IQC levels. Most tests in this study reached “acceptable” sigma performance or higher. These findings demonstrate that the Six Sigma approach is effective in monitoring and improving test quality by enabling the selection of appropriate IQC strategies for each parameter.